2010
DOI: 10.1074/jbc.m110.102145
|View full text |Cite
|
Sign up to set email alerts
|

New Roles for Cyclin E in Megakaryocytic Polyploidization

Abstract: Megakaryocytes are platelet precursor cells that undergo endomitosis. During this process, repeated rounds of DNA synthesis are characterized by lack of late anaphase and cytokinesis. Physiologically, the majority of the polyploid megakaryocytes in the bone marrow are cell cycle arrested. As previously reported, cyclin E is essential for megakaryocyte polyploidy; however, it has remained unclear whether up-regulated cyclin E is an inducer of polyploidy in vivo. We found that cyclin E is up-regulated upon stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 56 publications
0
46
0
1
Order By: Relevance
“…However, MKs are not subsequently blocked in 4N. Thus, abnormalities in the G1/S transition check point might also be present in the 4N MK 3,33,34 . In addition, it remains to understand why MYH9 does not accumulate in the cleavage furrow of MK in contrast to other cell types; in fact, myosin II isoform localization may depend on distinct upstream signalling pathways as shown in epithelial cells 31 .…”
Section: Discussionmentioning
confidence: 97%
“…However, MKs are not subsequently blocked in 4N. Thus, abnormalities in the G1/S transition check point might also be present in the 4N MK 3,33,34 . In addition, it remains to understand why MYH9 does not accumulate in the cleavage furrow of MK in contrast to other cell types; in fact, myosin II isoform localization may depend on distinct upstream signalling pathways as shown in epithelial cells 31 .…”
Section: Discussionmentioning
confidence: 97%
“…Cdk2 is the important kinase for endoreplication S phase in animal cells, although in the absence of Cdk2 in mammals, Cdk1 can act as a substitute (Ullah et al, 2009b). Cyclin E overexpression increases the ploidy of megakaryocytes (Eliades et al, 2010), suggesting that the Cyclin E/Cdk2 (Cdc2c -FlyBase) complex is the relevant kinase. Likewise, early work suggested that the Cyclin E/Cdk2 complex is the crucial, and perhaps only, CDK required for endoreplication in Drosophila (Lilly and Duronio, 2005).…”
Section: Primermentioning
confidence: 99%
“…After washing twice, cells were incubated with 0.5 mg/mL of RNase (Sigma-Aldrich), incubated with 50 mg/mL of propidium iodide, and analyzed by flow cytometry. 30 Colony forming units, TGF-b1, and TPO levels and Dnm2 fl/fl Pf4-Cre were plated into MegaCult collagen-based medium (STEMCELL Technologies) and cultured for 7 days in the presence of 10 ng/mL of IL-3, 20 ng/mL of IL-6, and 50 ng/mL of TPO (R&D Systems). Cells were dehydrated and fixed in acetone and stained for acetylcholinesterase activity.…”
Section: Mk Ploidymentioning
confidence: 99%